anonymous
  • anonymous
\[ \left( \begin{array}\ 1 & 0 &0 \\ 1 &0& 1\\ 0& 1 & 0 \end{array}\right)\] =A by cayley hamilton transformation method prove that \[A^n=A^n-2 +A^2-1\] and find \[A^50\]
Mathematics
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
Sorry my question is not appearing...
anonymous
  • anonymous
In a 3*3 matrix with a11=1,a12=0,a13=0,a21=1,a22=0,a23=1,a31=0,a32=1,a33=0...prove by cayley hamilton theorem that A^n= A^n-2+A^2-1.....also find A^50
anonymous
  • anonymous
@Jemurray3 @

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
The Cayley-Hamilton theorem says that matrices obey their own characteristic equations. So, \[det (A-\lambda I) = det\left(\begin{matrix}1-\lambda & 0 & 0 \\ 1 & -\lambda & 1 \\ 0 & 1 & -\lambda \end{matrix}\right) = \lambda^2(1-\lambda) -(1-\lambda) \] \[ = (\lambda^2 -1)(1-\lambda) = -\lambda^3+ \lambda^2 + \lambda - 1 = 0 \] implies that \[ -A^3 + A^2 + A - I = 0 \implies A^3 = A^2+ A - I \] We can use a proof by induction. Assume \[A^n = A^{n-2} + A^2 - I \] Then \[A^{n+1} = A\cdot A^n = A^{n-1} + A^3- A = A^{n-1} + A^2 + A - I - A\] \[ = A^{(n+1)-2} + A^2 - I \] Since we've already proved this for the case n = 2, it must hold for all n >= 2.
anonymous
  • anonymous
Furthermore, by the above theorem, \[A^{50} = A^{48} + A^2 - I = A^{46} + 2 ( A^2- I ) = A^{44} + 3(A^2- I) \] etc etc etc. Which yields the general formula (assuming that k is even) \[ A^k = A^2 + \frac{k-2}{2} \left( A^2 - I \right) \] So \[ A^{50} = A^2 + 24( A^2 - I ) = 25 A^2 - 24I\] A^2 is fairly easy to calculate: \[A^2 = \left(\begin{matrix}1 & 0 & 0 \\ 1 & 1 & 0 \\ 1 & 0 & 1 \end{matrix}\right)\] So finally, \[A^{50} = \left( \begin{matrix} 1 & 0 & 0 \\ 25 & 1 & 0 \\ 25 & 0 &1\end{matrix} \right) \]
anonymous
  • anonymous
but how did \[A^{48}+A^2-I\] turn into \[A^{46}+2(A^2-I)\]
anonymous
  • anonymous
Because via the proof above, \[ A^k = A^{k-2} + A^2 - I \]
anonymous
  • anonymous
thank you:)

Looking for something else?

Not the answer you are looking for? Search for more explanations.